“Neurodevelopmental disorder with microcephaly, epilepsy, and brain atrophy” with a novel mutation - Fathalla, Waseem; Salman, Farah (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
“Neurodevelopmental disorder with microcephaly, epilepsy, and brain atrophy” is a newly described disorder related to homozygous mutations in TRAPPC6B gene. Although nonspecific, the features of this disorder appear to have a characteristic course of postnatal progressive microcephaly that should raise the suspicion of this disorder. To the best of our knowledge, only eight cases were published in the literature. Here, we report a new case with a novel mutation and compare the clinical findings to the published cases. This case was not picked up by whole-exome sequencing but rather by whole-genome sequencing, emphasizing the importance of pursuing an etiological diagnosis in patients with otherwise unexplained progressive neurological disorders.
Keywords: Brain atrophy; epilepsy; neurodevelopmental disorder with microcephaly